STUDY OF PHILOSOPHY TERMINOLOGY IN WORLD LINGUISTICS - Abdujabborova Xilola Rakhmatilla's daughter; Abdujabborova Hilola Rahmatilla kisi (American Journals Publishing, 2022)
This article highlights the study of philosophy terminology by world linguists. The main focus is on the study of terminology by Western scholars and MDH countries, especially Russian and Tajik linguists. The extent to which terminology of this field has been studied and the general and different aspects of scientific research will be studied.
Keywords: philosophy, philosophy terminology, copyright term, dictionary, research, article.